Electronic and Magnetic Properties of Iron Clusters Encapsulated in Carbon Nanotubes (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have made theoretical study of the electronic and magnetic properties of iron clusters  encapsulated in carbon nanotubes using density functional theory. We have considered  cluster encapsulated inside finite pieces of single wall zigzag nanotubes of indices (11,0) and  (10,0). Finite zigzag nanotubes have a peculiar magnetic structure, the ground state is an  antiferromagnetic spin singlet S=0. The local spin polarization oscillates along the direction of  the nanotubes axis and is small, except at the two ends of the edges of the nanotubes. We have  studied the encapsulation of iron atoms and small Fenclusters n = 2, 4,8 in a short (10,0) tube.  By the constraints imposed by the cylindrical geometry of a narrow nanotubes, we have  considered the encapsulation of an isomer of F12with an elongated structure. We have also  considered the encapsulation of the lowest energy, icosahedral structure of F12. The free  elongated Fe12isomer presented a strong ferromagnetic spin coupling giving rise to a large  magnetic moment. The distortion in the density of state of the iron cluster is much smaller  preserving the strong ferromagnetic character. There is some p-d hybridization between the  nanotubes and the cluster states, mainly around the Fermilevel. The loweswt unoccupied  molecular orbital of the pristine zigzag nanotubes becomes partially occupied due to charge  transfer from the cluster to the nanotubes. We have analysed the interplay between the  singular magnetic properties of the finite zigzag nanotubes and the large magnetization of the  encapsulated iron clusters. The calculations indicated that the magnetism is confined within  the iron aggregates, with small reduction of the magnetic moment per atom with respect to  the free iron clusters. The magnetic moment per atom result enhanced with respect to those of  bulk iron, due to the reduced coordination of the metal atoms. The obtained results were  found in good agreement with previously obtained results.